Co-Culture Anoxygenic Photosynthetic Bacteria With Bacillus sp. Isolated From Hanura Beach Against Vibrio sp. - Sumardi Sumardi; Salman Farisi; Christina Nugroho Ekowati; Sundari Ayu Oktalia (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2019)
A mangrove forest ecosystem is a place where many special Bacillus sp. found. This study aims to obtain Bacillus sp. isolates that can inhibit the growth of Vibrio sp. This study was conducted by selecting 77 Bacillus sp. isolates from the Hanura mangrove forest area. In addition, selected bacteria were tested for salt stress, pH stress, pathogenicity test, and antibiotic susceptibility test. Selected isolates were cultivated together with Vibrio sp. for 7 days. Bacillus sp. and Vibrio sp. cultured again with the addition of anoxygenic photosynthetic bacteria for 4 days. From the results of the initial selection, 4 isolates could inhibit the growth of Vibrio sp. The final results showed that Bacillus IL2K8 isolates were known to inhibit the growth of Vibrio sp., can grow at salinity 0%, 3%, 6% and pH 7 and pH 10. IL2K8 isolates are not pathogenic, resistant to amplicin antibiotics, streptomycin, nalidixic acid, and chloramphenicol but sensitive to trimethoprim antibiotics. In the joint culture of liquid media IL2K8 together with Anoxygenic Photosynthetic Bacteria (APB) isolates IL2K8 can inhibit the growth of Vibrio sp.